Chromosome Analysis Using Benchtop Flow Analysers and High Speed Cell Sorters. Issue 3 (17th December 2018) - Ng, Bee L.; Fu, Beiyuan; Graham, Jennifer; Hall, Christopher; Thompson, Sam
Abstract: The use of the DNA dyes Hoechst (HO) and chromomycin A3 (CA3) has become the preferred combination for the bivariate analysis of chromosomes from both human and animals. This analysis requires a flow cytometer equipped with lasers of specific wavelength and of higher power than is typical on a conventional bench top flow cytometer. In this study, we have investigated the resolution of chromosome peaks in a human cell line with normal flow karyotype using different combinations of DNA dyes on a number of flow cytometers available in a flow cytometry core facility. Chromosomes were prepared from the human cell line using a modified polyamine isolation buffer. The bivariate flow karyotypes of different DNA dyes combination; 4′‐6‐diamidino‐2‐phenylindole (DAPI) or Hoechst with propidium iodide (PI), obtained from different flow cytometers were compared to the reference flow karyotype of DAPI or Hoechst with chromomycin A3, generated from a Mo‐Flo cell sorter using laser power settings of 300 mW each of UV and 457 nm. Good chromosome separation was observed in most of the flow cytometers used in the study. This study demonstrates that chromosome analysis and sorting can also be performed on benchtop flow cytometers equipped with the standard solid state 488 and 355 nm lasers, using a DNA dye combination of DAPI or Hoechst with PI. © 2018 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry. Abstract :